The Savvy Survey #5: The Process for Developing Survey Questions - Glenn D. Israel; Jessica L. Gouldthorpe (EDIS)
A useful process for developing a high-quality questionnaire follows four steps. Brainstorm questions on a topic. Review the literature for concepts, questions, and indices. Collect ideas for questions and wording choices through focus groups or key informant interviews. And select questions linked to a program’s logic model. Each of these steps is discussed in this 3-page fact sheet written by Glenn D. Israel and Jessica L. Gouldthorpe and published by the UF Department of Agricultural Education and Communication, August 2013.